Conserved genomic and amino acid traits of cold adaptation in subzero-growing Arctic permafrost bacteria. Issue 4 (8th March 2018) - Raymond-Bouchard, Isabelle; Goordial, Jacqueline; Zolotarov, Yevgen; Ronholm, Jennifer; Stromvik, Martina; Bakermans, Corien; Whyte, Lyle G
Abstract: Permafrost accounts for 27% of all soil ecosystems and harbors diverse microbial communities. Our understanding of microorganisms in permafrost, their activities and adaptations, remains limited. Using five subzero-growing (cryophilic) permafrost bacteria, we examined features of cold adaptation through comparative genomic analyses with mesophilic relatives. The cryophiles possess genes associated with cold adaptation, including cold shock proteins, RNA helicases, and oxidative stress and carotenoid synthesis enzymes. Higher abundances of genes associated with compatible solutes were observed, important for osmoregulation in permafrost brine veins. Most cryophiles in our study have higher transposase copy numbers than mesophiles. We investigated amino acid (AA) modifications in the cryophiles favoring increased protein flexibility at cold temperatures. Although overall there were few differences with the mesophiles, we found evidence of cold adaptation, with significant differences in proline, serine, glycine and aromaticity, in several cryophiles. The use of cold/hot AA ratios of >1, used in previous studies to indicate cold adaptation, was found to be inadequate on its own. Comparing the average of all cryophiles to all mesophiles, we found that overall cryophiles had a higher ratio of cold adapted proteins for serine (more serine), and to a lesser extent, proline and acidic residues (fewer prolines/acidic residues). Abstract : This is the first large scale study focused on identifying genomic and molecular traits associated with cold adaptation in subzero-growing bacteria from permafrost.